Nitrate Is Crucial for the Proliferation of Gut Escherichia coli Caused by H9N2 AIV Infection and Effective Regulation by Chinese Herbal Medicine Ageratum-Liquid - Zhang, Xinheng; Zhao, Qiqi; Wu, Che; Xie, Zi; Ci, Xiaotong; Li, Hongxin; Lin, Wencheng; Zhang, Huanmin; Xie, Qingmei (Frontiers in Microbiology, 2020)
H9N2 avian influenza virus (AIV) infection in chickens is often accompanied by secondary bacterial infection, but the mechanism is unclear. The aim of the present study was to reveal that mechanism and explore non-antibiotic treatment. 16s rRNA sequencing and metabonomics were performed in the intestinal contents of chickens infected with H9N2 AIV or H9N2 AIV and fed with ageratum-liquid (AL) to reveal the metabolite that promote intestinal Escherichia coli (E. coli) proliferation caused by H9N2 AIV, as well as to determine the regulatory effect of AL. It was found that H9N2 AIV infection led E. coli to become the dominant gut microbe and promoted E. coli translocation from the intestinal tract to the visceral tissue through the damaged intestinal barrier. H9N2 AIV infection induces inflammation in the intestinal mucosa and promotes the secretion and release of nitrate from the host intestinal epithelium. In addition, nitrate promoted E. coli proliferation in the inflamed intestinal tract following H9N2 AIV infection. Furthermore, Chinese herbal medicine AL can restore intestinal homeostasis, inhibit the production of nitrate in the intestinal epithelium and effectively prevent the proliferation and translocation of E. coli in the intestines. This is the first report on the mechanism of E. coli secondary infection induced by H9N2 AIV, where herbal medicine AL was shown to have a good preventive effect on the secondary infection.